Audiovisual speech perception in children with autism spectrum disorders: Evidence from visual phonemic restoration. - Irwin, Julia; Avery, Trey; Kleinman, Daniel; Landi, Nicole (Journal of autism and developmental disorders, 2021)
Children with autism spectrum disorders have been reported to be less influenced by a speaker’s face during speech perception than those with typically development. To more closely examine these reported differences, a novel visual phonemic restoration paradigm was used to assess neural signatures (event-related potentials [ERPs]) of audiovisual processing in typically developing children and in children with autism spectrum disorder. Video of a speaker saying the syllable /ba/ was paired with (1) a synthesized /ba/ or (2) a synthesized syllable derived from /ba/ in which auditory cues for the consonant were substantially weakened, thereby sounding more like /a/. The auditory stimuli are easily discriminable; however, in the context of a visual /ba/, the auditory /a/ is typically perceived as /ba/, producing a visual phonemic restoration. Only children with ASD showed a large /ba/-/a/ discrimination response in the presence of a speaker producing /ba/, suggesting reduced influence of visual speech. © 2021, The Author(s), under exclusive licence to Springer Science+Business Media, LLC part of Springer Nature.
Keywords: Auditory Perception; Autism Spectrum Disorder; Child; Cues; Evoked Potentials; Humans; Speech; Speech Perception; Visual Perception; association; autism; child; dept.psy; evoked response; hearing; human; peer-reviewed; speech; speech perception; vision